An evaluation of Arabic for Human Sciences students programme - Zubir, Badri Najib; Mohammad Lotfie, Maskanah; Mohd Ghalib, Mohd Feham (2011)
The learning of the Arabic language has been included as a requirement in IIUM’s Human Sciences undergraduate curriculum mainly as one of the means to effectively realize the University’s philosophy in augmenting the Islamicisization of contemporary human knowledge. Thus, all students majoring in communication, English linguistics, English literature, history, political science, psychology, sociology and anthropology are required to learn Arabic up to the intermediate level. An evaluation of the programme has been carried out to ensure that the teaching and learning process of the Arabic courses could be improved and be made relevant and useful to the students. With the improvement of the current programme in mind, an evaluative preliminary survey has been carried among students who were in their final level of the Arabic programme. Respondents of the study (n = 44) completed a questionnaire that is also consisted of an open-ended section. The students’ responses provide insightful thoughts on the issue at hand, including their support for the programme and practical ideas to improve it. The findings of this study will be valuable in important policy-making decisions that will shape the revised curriculum of the Arabic programme.